FCD use, Firm Value and Corporate Governance - Mara Patrícia Ferreira da Silva (2017)
This study examines the impact of the use of currency derivatives on firm value using a sample of non-financial foreign firms from 14 countries of the European Union that are cross-listed on major stock exchanges between 2005 and 2015. All the results are obtained from an OLS regression and also from the quantile regression approach, to correct standard errors from within cluster dependence. We hypothesize that currency derivatives use is associated with firm value in companies with a strong firm-specific and country-specific corporate governance. The results reveal a positive association between the use of currency derivatives and firm value in firms which have strong internal corporate governance and from countries with Scandinavian Civil Law. This could mean that in the European context the legal family with the strongest investor protection rights is the Scandinavian family. We also found evidence that the legal family with the lowest investor protection rights is the French Commercial Code. This study is important for all the investors that want to understand which countries have the best mechanisms to protect them.